Pathogenic Free-Living Amoebae Isolated From Contact Lenses of Keratitis Patients - HAJIALILO, Elham (Iran J Parasitol, 2015)
BACKGROUND: Free-living amoeba (FLA)-related keratitis is a progressive infection of the cornea with poor prognosis. The present study aimed to investigates the contact lenses of patients with keratitis for pathogenic free-living amoebae. METHODS: Overall, 62 contact lenses and their paraphernalia of patients with keratitis cultured and tested for the presence of free-living amoebae using morphological criteria. Unusual plates including plates containing mix amoebae and Vermamoeba were submitted to molecular analysis. RESULTS: Out of 62 plates, 11 revealed the outgrowth of free living amoeba of which 9 were Acanthamoeba, one plates contained mix amoebae including Acanthamoeba and Vermamoeba and one showed the presence of Vermamoeba. These two latter plates belonged to patients suffered from unilateral keratitis due to the misused of soft contact lenses. One of the patients had mix infection of Acanthamoeba (T4) and V. vermiformis meanwhile the other patient was infected with the V. vermiformis. CONCLUSION: Amoebic keratitis continues to rise in Iran and worldwide. To date, various genera of free-living amoebae such as Vermamoeba could be the causative agent of keratitis. Soft contact lens wearers are the most affected patients in the country, thus awareness of high-risk people for preventing free-living amoebae related keratitis is of utmost importance.